Applying transdisciplinary sustainability transitions research in international social work doctoral training. Issue 7 (3rd October 2022) - Matthies, Aila-Leena; Hermans, Koen; Leskošek, Vesna
ABSTRACT: In the last 15 years, transdisciplinary research of sustainability transitions has become an increasingly powerful approach. We discuss it as a perspective for social work discipline, and as a theoretical-conceptual frame of a new international doctoral training and research programme in social work taking place in seven European countries. In our qualitative study, we investigate how the participating social work doctoral students reflect upon transdisciplinarity and understand the interconnectivity between environmental, ecological, and social sustainability transitions—which is widely recognised as a highly complex challenge of sustainability. The data used included the students' learning diaries from the first summer school of this programme. As core findings of the analysis five joint themes expressing the interconnectivity emerged from the data: the indispensable role of nature for all life; the economy-based causes of unsustainability; the role of human rights; the researchers' own ways of life; and the practice-relevance for SW. Our results support recent theoretical arguments that transdisciplinarity comprises not only a disciplinary thinking but a way of being, where the holistic lives of researchers merge with the content of their work. Regarding our analysis of the pedagogical and didactic arrangements promoting transdisciplinary thinking, we can encourage direct collaboration and teaching inputs with other disciplines and demonstrable practice applications.